IDENTIFIKASI KEPUTUSAN PEMBELIAN KONSUMEN KEDAI KOPI MELALUI IKLAN MEDIA SOSIAL INSTAGRAM - resika, resika (Majalah Ilmiah Manajemen STIE Aprin Palembang, 2023)
Social media has become a partner in carrying out community activities, including in running a business. Currently, social media is one of the company's tools for placing advertisements, one of which is on Instagram to increase costumer interest. This study aims to determine how much advertising influences consumer buying decisions at Rich Coffee Shop. This quantitative descriptive study used a probability samplng technique with a simple random sampling method with a total of 96 respondents who visited Rich Coffee Shop who filled out a questionnaire. Questionnaire that has been adjusted to the Likert scale which has been teste for its validity and reliability. Data analysis techniques using validity test, reliability test, and simple linear regression test. The results of this study indicate that data analysis and discussion of advertising have a positive influence on consumer purchasing decisions. These results prove that Instagram advertising can increase consumer decisions.